Tellurium segregation-induced intergranular corrosion of GH3535 alloys in molten salt. (January 2022) - Jiang, Li; Wang, Kai; Leng, Bin; Ye, Xiang-Xi; Chen, Shuang-Jian; Liu, Ren-Duo; Liang, Jian-Ping; Li, Chao-Wen; Li, Zhi-Jun
Abstract: The catastrophic intergranular cracking had been observed in the low-Cr alloy components in the primary loop of molten salt reactor. Such cracking was related to the coupling effect of fission product tellurium (Te) and fuel salts, whose atomic-level mechanism has puzzled researchers for many decades. In this work, combining multi-scale characterization techniques and theoretical calculations, it was found that Te segregation at grain boundaries can reduce the diffusion barrier of active element along grain boundaries and cause the nano-voids, which further evolve into the intergranular cracking. Highlights: Dissolution of active elements causes the formation of nanovoids at grain boundaries. Nanovoids evolve into the intergranular cracking in the manner of local collapse. Te segregation at grain boundaries reduces the diffusion barrier of active element. Te segregation induces intergranular corrosion of alloys in molten salt.